1984
DOI: 10.1111/j.1755-3768.1984.tb08447.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors in a Finnish Rural Population

Abstract: Refractive errors in 611 persons living in a rural area were examined. Males numbered 281 and females 330. The age range was from 6 to 85 years. In 73 (11.9%) persons the refraction was myopic (SER less than or equal to 0.5 D) and in 173 (28.3%) hyperopic (SER greater than or equal to + 2 D). Myopia was most frequently detected in persons aged 21-30 years (22.6%), and the proportion of myopia decreased towards both extremes of age. In all age groups females were more myopic than males. In persons aged 21-60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…Participants with manual occupations and those living in rural areas were also more likely to be myopic and have astigmatism. Some of these findings contrast with other populationbased studies, which have shown associations between myopia, higher education levels, professional occupations and residence in urban areas 25,26,32,33,40,43,46,48,51 (in support of the use-abuse theory of myopia). There are, however, exceptions to these trends: The Baltimore Eye Study showed that the association between years of education and myopia was stronger for white persons than for black persons, 35 the Chennai Study (India) showed a higher prevalence of myopia in participants living in rural areas, 49 and the Bangladesh study showed a significantly lower risk of myopia with literacy, urban living, and nonmanual occupation.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Participants with manual occupations and those living in rural areas were also more likely to be myopic and have astigmatism. Some of these findings contrast with other populationbased studies, which have shown associations between myopia, higher education levels, professional occupations and residence in urban areas 25,26,32,33,40,43,46,48,51 (in support of the use-abuse theory of myopia). There are, however, exceptions to these trends: The Baltimore Eye Study showed that the association between years of education and myopia was stronger for white persons than for black persons, 35 the Chennai Study (India) showed a higher prevalence of myopia in participants living in rural areas, 49 and the Bangladesh study showed a significantly lower risk of myopia with literacy, urban living, and nonmanual occupation.…”
Section: Discussioncontrasting
confidence: 69%
“…[42][43][44][45] The men in our survey had a slightly higher prevalence of myopia than did the women, as has been reported in other studies. 26,37,[47][48][49] The prevalence of hypermetropia (50.7%) was considerably higher than that in most Asian studies, being closer to that in populations of predominantly European or African descent. The relationship between hypermetropia and age showed a pattern similar that in to studies from Asia and Barbados, [25][26][27]31,33,39,49 with a rise to maximum levels in the 50-to 59-year-old group, followed by a decline in later years.…”
Section: Discussionmentioning
confidence: 98%
“…When looking at first-eye surgeries separately, however, and assuming that the refraction in the untouched fellow eye registered postoperatively resembles the preoperative refraction in the first eye, presumably myopic eyes become more myopic than planned and hyperopic eyes become more hyperopic. We are aware that this is based on assumptions; however, previous Nordic studies 18,19 found that anisometropia exceeds 1.00 D in only 7% to 9% of individuals. Therefore, we think our assumptions are reasonable.…”
Section: Discussionmentioning
confidence: 94%
“…Refractive errors are common in the Beaver Dam Eye Study cohort, with 26.2% being myopic (-0.75 diopters or more negative) and 49.0% being hyperopic (+0.75 diopters or more positive). Environmental factors have been reported to be associated with refraction, the most notable being near-work or educational attainment which is used as a surrogate measure for nearwork1-5. We have recently reported that longer axial length was associated with an increase in years of education and height within this cohort.…”
Section: Introductionmentioning
confidence: 84%